Overconfidence and Gender Equality in the Labor Market - Spencer Bastani; Thomas Giebe; Oliver Gürtler (Center for Economic Studies and ifo Institute (CESifo), 2023)
Gender differences in overconfidence have been extensively documented in the empirical literature, but the implications for labor market outcomes are not well understood. In this paper, we analyze how men's relatively higher overconfidence, combined with competitive job incentives, affects gender equality in the labor market and discuss policy implications. The vehicle of analysis is a promotion-signaling model in which wages are realistically determined by market forces. We find that overconfident workers exert more effort to be promoted, and even though they have lower expected ability conditional on promotion, they are more likely to be promoted and experience superior wage growth. Because overconfident workers compete fiercely, they incur higher effort costs and discourage their peers, and we find that overconfidence can be either self-serving or self-defeating.
Keywords: C72; D91; J16; J24; M51; M52; 330; overconfidence; promotion; competition; gender gap; tournament; theory